Within-population genetic diversity and population structure of Plasmodium knowlesi merozoite surface protein 1 gene from geographically distinct regions of Malaysia and Thailand - Ahmed, Md Atique; Chu, Ki Back; Vythilingam, Indra; Quan, Fu-Shi (BioMed Central, 2018)
Background: The C-terminal 42 kDa domain of Plasmodium knowlesi merozoite surface protein 1 (PkMSP1) is a potential asexual blood-stage vaccine candidate, however, only a limited number of clinical isolates have been analysed from Malaysia and no inter-country comparative diversity study has been conducted. In the present study, nucleotide diversity, haplotypes and natural selection levels of pkmsp1 in clinical samples from geographically distinct regions of Malaysia and Thailand were investigated. The overall population structure of the parasite from the region was determined. Methods: Eleven full-length pkmsp1 sequences obtained from clinical isolates of Malaysia along with the H-strain were downloaded from the database for domain wise characterization of pkmsp1 gene. Additionally, 76 pkmsp-1 42 sequences from Thailand and Malaysia were downloaded from the database for intra and inter-population analysis. DnaSP 5.10 and MEGA 5.0 software were used to determine genetic diversity, polymorphism, haplotypes and natural selection. Genealogical relationships were determined using haplotype network tree in NETWORK software v5.0. Population genetic differentiation index (F ST ) of parasites were analysed using Arlequin v3.5. Results: Sequence analysis of 11 full-length pkmsp1 sequences along with the H-strain identified 477 (8.4%) polymorphic sites, of which 107 were singleton sites. The overall diversity observed in the full-length genes were high in comparison to its ortholog pvmsp1 and the 4 variable domains showed extensive size variations. The nucleotide diversity was low towards the pkmsp1-42 compared to the conserved domains. The 19 kDa domain was less diverse and completely conserved among isolates from Malaysian Borneo. The nucleotide diversity of isolates from Peninsular Malaysia and Thailand were higher than Malaysian Borneo. Network analysis of pkmsp1-42 haplotypes showed geographical clustering of the isolates from Malaysian Borneo and grouping of isolates from Peninsular Malaysia and Thailand. Population differentiation analysis indicated high F ST values between parasite populations originating from Malaysian Borneo, Peninsular Malaysia and Thailand attributing to geographical distance. Moderate genetic differentiation was observed for parasite populations from Thailand and Peninsular Malaysia. Evidence of population expansion and purifying selection were observed in all conserved domains with strongest selection within the pkmsp1-42 domain. Conclusions: This study is the first to report on inter country genetic diversity and population structure of P. knowlesi based on msp1. Strong evidence of negative selection was observed in the 42 kDa domain, indicating functional constrains. Geographical clustering of P. knowlesi and moderate to high genetic differentiation values between populations identified in this study highlights the importance of further evaluation using larger number of clinical samples from Southeast Asian countries.